2003
DOI: 10.1002/anie.200352405
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Sensing with a Fluorescent Thin‐Film Hydrogel

Abstract: Sweetness and light: A fluorescent thin‐film hydrogel that contains a covalently bound boronic‐acid‐functional quencher (Q) and a fluorescent dye (F; see Figure) continuously senses glucose under physiological conditions through binding of the sugar (S) to a labeled receptor (R).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 13 publications
(6 reference statements)
0
99
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, only a few of these membranes are capable of simultaneously reducing the large glucose/O 2 ratio and releasing tissue response modifiers that suppress inflammation and fibrotic encapsulation. With this in mind, a stacked configuration of outer membranes based on ultrathin LBL-assembled films and PVA hydrogels are currently shown to provide a powerful combination to regulate glucose with the inner membrane and improve its ratio with O 2 , while the outer PVA hydrogel layer can be loaded with drug-releasing microspheres capable of suppressing inflammation in excess of 1 month.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, only a few of these membranes are capable of simultaneously reducing the large glucose/O 2 ratio and releasing tissue response modifiers that suppress inflammation and fibrotic encapsulation. With this in mind, a stacked configuration of outer membranes based on ultrathin LBL-assembled films and PVA hydrogels are currently shown to provide a powerful combination to regulate glucose with the inner membrane and improve its ratio with O 2 , while the outer PVA hydrogel layer can be loaded with drug-releasing microspheres capable of suppressing inflammation in excess of 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…2 Following device implantation, this is further compounded by inflammation, biofouling, and fibrotic encapsulation, which lead to additional variations in glucose-to-oxygen ratios. [1][2][3][4][5][6] While a number of semipermeable membranes have been developed to optimize the glucose-to-oxygen ratio, [7][8][9][10][11][12][13][14][15][16][17][18] only a few systems have been used with drugreleasing hydrogels, 17,18 designed to suppress inflammation, biofouling, and fibrotic encapsulation. The typical approach to counter both these issues is the use of overlaid membranes in which the inner membrane limits glucose diffusion and the outer membrane counters fibrotic encapsulation.…”
mentioning
confidence: 99%
“…During the last two decades chemical indicators have been immobilized in polymeric matrices mainly by simple impregnation, 3 by doping 53 or by covalent attachment. 54 Other strategies such as electrostatic layer-by-layer assembly have also been used. 55 Polymers used in sensor devices either participate in the sensing mechanism or they are used to immobilize the component responsible for analyte sensing.…”
Section: Fluorescent Polymersmentioning
confidence: 99%
“…Covalent attachment of the fluorescent molecules into polymeric materials is possible after polymerization if the polymer contains reactive functional groups, 77 or by co-polymerization with a fluorescent polymerizable monomer. 54 Initially, covalent functionalization of polymers with fluorescent molecules was performed by covalent attachment of fluorophores to natural polymers as cellulose. For example, in 1992 Wolfbeis et al already reported the immobilization of pH sensitive dyes in cellulose matrices, 78 and recently Ueno's group described the covalent immobilization of dansyl functionalized cyclodextrins in a cellulose membrane for the detection of neutral molecules (Fig.…”
Section: Fluorescent Polymersmentioning
confidence: 99%
“…It is possible to "tune" the fluorescence to be particularly sensitive in the hypoglycemic range, and due to the fundamental mechanism by which fluorescence occurs, it is intrinsically sensitive and yields low noise measurements when compared with other optical measurement methods. [7][8][9] The study described here examined the 24 h accuracy and performance in volunteers with type 1 diabetes of a second-generation prototype of the GluCath ® system, an intravascular continuous glucose monitoring (IV-CGM) system intended for use in hospitalized patients. A previous study similarly examined a first-generation device at 8 h durations.…”
Section: Introductionmentioning
confidence: 99%